Napa Soil-Derived NiAl₂O₄/MWCNT-Modified Glassy Carbon Electrode for Cd²⁺ Detection - Ayu, Stevy Dara; Mawardi, Mawardi; Sanjaya, Hary; Ningsih, Sherly Kasuma Warda; Suryani, Okta (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Cadmium ions (Cd²⁺) are toxic environmental pollutants that require sensitive and reliable detection methods. This study aimed to develop a NiAl₂O₄/MWCNT-modified glassy carbon electrode (GCE) using NiAl₂O₄ synthesized from napa soil as a sustainable local resource for electrochemical Cd²⁺ detection. The electrode was fabricated through a drop-casting method and characterized using cyclic voltammetry. The electrochemical performance of the modified electrode was evaluated for Cd²⁺ detection, including the effects of supporting electrolytes, stability, and analytical performance. The results showed that the incorporation of NiAl₂O₄ and multi-walled carbon nanotubes significantly enhanced the electrochemical response and electron-transfer kinetics compared with the bare GCE. Among the tested electrolytes, 0.1 M KCl provided the highest current response. The sensor exhibited a linear response toward Cd²⁺ concentrations in the range of 1–4 mM with a regression equation of y = 14.332x + 39.895 and a correlation coefficient (R²) of 0.9941. The limit of detection (LOD) and limit of quantification (LOQ) were calculated as 0.2988 mM and 0.9961 mM, respectively. In addition, the electrode demonstrated good stability during repeated measurements. These findings indicate that the napa soil-derived NiAl₂O₄/MWCNT-modified GCE is a promising, low-cost, and environmentally sustainable platform for Cd²⁺ monitoring.